Designing future experiences of the everyday: Pointers for methodical expansion of sustainability transitions research. (March 2021) - GarduñoG arcía, Claudia; Gaziulusoy, İdil
Highlights: The emerging field of experiential futures can potentially contribute to the methodical expansion of transitions research. Everydayness might make futures relatable while fictional narratives might enable participants to engage emotionally. Real emotional responses to vicarious experiences generate memories that might allegedly lead to behavioural change. The further development of experiential futures requires transdisciplinary collaborations. Abstract: It is critical now that we direct all our efforts at transitions to post-carbon and sustainable futures. Currently, transitions are mostly handled by select expert groups who generate transition visions, scenarios and pathways, feed their findings into policy-making processes, thereby locking-in "futures" on behalf of the wider public. Scholars from a variety of disciplinary backgrounds are searching for more effective means to engage and empower citizens to effectively comprehend and actively take part in futuring processes. Experiential futures is an emerging field that connects experience design and futures studies. Experiential scenarios aim to create real memories of virtual events so that alternative futures can be understood and deliberated better by publics. This article maps contributions belonging to different disciplinary fields (including speculative design, literature studies, and psychology) to explore the means by which the everyday in futures could be virtually or vicariously experienced, aiming to contribute into the theoretical and methodological base of experiential futures. Our findings suggest that people's ability for being immersed into a story is positively correlated with their empathic capacity . Immersion seems to be most successfully achieved when the experience shares some level of familiarity with people's everyday reality and when the narrative is logically convincing. In addition, our findings indicate that avid fiction readers are more easily immersed in alternative scenarios than those who are not. Our findings have significant implications for designing future experiences of the everyday, therefore, on theory and methods of sustainability transitions.